Integration of quantitative imaging biomarkers in clinical trials for MR-guided radiotherapy: Conceptual guidance for multicentre studies from the MR-Linac Consortium Imaging Biomarker Working Group. (August 2021) - van Houdt, Petra J.; Saeed, Hina; Thorwarth, Daniela; Fuller, Clifton D.; Hall, William A.; McDonald, Brigid A.; Shukla-Dave, Amita; Kooreman, Ernst S.; Philippens, Marielle E.P.; van Lier, Astrid L.H.M.W.; Keesman, Rick; Mahmood, Faisal; et al.
Abstract: Quantitative imaging biomarkers (QIBs) derived from MRI techniques have the potential to be used for the personalised treatment of cancer patients. However, large-scale data are missing to validate their added value in clinical practice. Integrated MRI-guided radiotherapy (MRIgRT) systems, such as hybrid MRI-linear accelerators, have the unique advantage that MR images can be acquired during every treatment session. This means that high-frequency imaging of QIBs becomes feasible with reduced patient burden, logistical challenges, and costs compared to extra scan sessions. A wealth of valuable data will be collected before and during treatment, creating new opportunities to advance QIB research at large. The aim of this paper is to present a roadmap towards the clinical use of QIBs on MRIgRT systems. The most important need is to gather and understand how the QIBs collected during MRIgRT correlate with clinical outcomes. As the integrated MRI scanner differs from traditional MRI scanners, technical validation is an important aspect of this roadmap. We propose to integrate technical validation with clinical trials by the addition of a quality assurance procedure at the start of a trial, the acquisition of in vivo test-retest data to assess the repeatability, as well as a comparison between QIBs from MRIgRT systems and diagnostic MRI systems to assess the reproducibility. These data can be collected with limited extra time for the patient. With integration of technical validation in clinical trials, the results of these trials derived on MRIgRT systems will also be applicable for measurements on other MRI systems. Highlights: Daily imaging is feasible on integrated MRI-guided radiotherapy (MRIgRT) systems. This will advance quantitative imaging biomarker (QIB) research in oncology. QIBs have the potential to personalise radiotherapy treatment. This paper presents a roadmap towards clinical use of QIBs on MRIgRT systems. Technical validation should be integrated in clinical trials on MRIgRT systems.